ANALISIS KESULITAN SISWA SMP DI ISLAMIC BOARDING SCHOOL DALAM MENYELESAIKAN SOAL PADA MATERI BANGUN RUANG SISI DATAR - Ai Fatimah; Ratni Purwasih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
Difficulties in solving a mathematical problem are still experienced by many students. This difficulty will be analyzed by researcher in Junior High School students at the Islamic Boarding School in solving the problem description of the subject matter of flat side geometry. This research was conducted in class IX students of Al-Ittihad Plus Junior High School Cianjur in the even semester of the 2019/2020 school year. This type of research used in this study is a case study. The research instrument used was a written test. The subjects of this study uses stratified random sampling. Six research subjects were chosen consisting of two subjects with high, moderate and low mathematical abilities in terms of the results of tests given to 36 prospective subjects. In this case study students were given a test by the researcher, then after being given the test the researcher conducted an open interview to the students to produce data. This test is a measuring tool in analyzing student difficulties regarding the subject matter of flat side geometry cube, cuboid, prysm and pyramid. An open interview was conducted to find out more deeply about the difficulties experienced by students. It was cocluded that the results of this case study were students with high, moderate and low levels of mathematical ability had difficulty in: (1) determining the mathematical model in solving the problems presented correctly, (2) determining the concepts and strategies in solving prolems and (3) understanding mathematical problems.